2021
DOI: 10.3390/plants10081488
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Molecular Networking and LC-MS/MS Profiling in Investigating the Interrelationships between the Antioxidant and Antimicrobial Properties of Curculigo latifolia

Abstract: Curculigo is a potent plant with a variety of traditional uses, such as anti-oxidant, anti-diabetic, anti-tumor, anti-bacterial, anti-cancer, anti-osteoporosis, and wound-healing. The comprehensive profiling of the Curculigolatifolia metabolome was carried out by generating a molecular network (MN) from Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) data to profile the methanol extract and correlating them with their antioxidant (2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), total phenolic contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
2
12
1
Order By: Relevance
“…One or two types of extracts that do not correlate with the test results of the three methods used may be affected by the chemical content of each extract in terms of content and compound group. Several studies relevant to the potential of C. latifolia to reduce DPPH radicals showed that ethanol and aqueous extracts from plant roots were the most potent antioxidants [ 9 , 10 , 12 , 33 ]. In the ethanol extract of leaf organs, the present study showed a strong activity in reducing DPPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One or two types of extracts that do not correlate with the test results of the three methods used may be affected by the chemical content of each extract in terms of content and compound group. Several studies relevant to the potential of C. latifolia to reduce DPPH radicals showed that ethanol and aqueous extracts from plant roots were the most potent antioxidants [ 9 , 10 , 12 , 33 ]. In the ethanol extract of leaf organs, the present study showed a strong activity in reducing DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the compounds of extracts was carried out using a liquid chromatography-mass spectroscopy (LC-MS) system using the modified methods in [ 32 , 33 ]. A Waters Acquity UPLC I-Class equipped with a Xevo G2-XS QToF mass spectrometer with an ESI source (capillary 2 kV, temperature 120°C) was used to generate mass spectra.…”
Section: Methodsmentioning
confidence: 99%
“…are also used as eye drops, and to stop bedwetting in young children. Keliangauan (Curculigo latifolia) is commonly used to eliminate the bitter taste on the tongue when sick by eating the ripe fruit because it tastes sweet and can retain its sweet taste (Ishak et al 2013;Nie et al 2013;Mad Nasir et al 2021).…”
Section: Medicinal Plants By Type Of Diseasementioning
confidence: 99%
“…The de-replication information was then collected by MN, which compares all MS/MS spectra of studied compounds and groups them according to their spectral similarity, thus allowing the visualization of all structurally related molecules within the same cluster and structurally different molecules distributed in different clusters [ 9 ]. This approach thus provides new ways to navigate the metabolome of biological samples by providing key information about the analogies between detected metabolites [ 10 ]. The main interest of molecular networks is that they can be used to exploit numerous MS/MS spectra without prior knowledge of the chemical composition of the samples, and the data obtained can be directly correlated to antimicrobial and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%